Berberine decorated zinc oxide loaded chitosan nanoparticles a potent anti cancer agent against breast cancer - Fatemeh Esnaashari; Hojjatolah Zamani; Hossein Zahmatkesh; Mojtaba Soleimani; Golnesa Amirian Dashtaki; Behnam Rasti (Scientific Reports)
Abstract Breast cancer ranks as the second leading reason of cancer mortality among females globally, emphasizing the critical need for novel anticancer treatments. In current work, berberine-zinc oxide conjugated chitosan nanoparticles were synthesized and characterized using various characterization techniques. The cytotoxic effects of CS-ZnO-Ber NPs on MCF-7 cells were assessed using the MTT assay. Also, annexin V-FITC/PI double staining, Hoechst 33,342 staining, caspases-8 and 9 activity assays, and cell cycle analysis were performed. Furthermore, the mRNA levels of Bax and Bcl-2 genes were quantified using qPCR. Additionally, cell migration was evaluated using a scratch assay. The IC50 value of NPs against MCF-7 cells measured 7.41 µg/mL. Apoptosis induction in NP-treated cells was confirmed by Annexin V/PI staining, accompanied by the observation of condensed chromatin and fragmented DNA. Moreover, the pro-apoptotic potential of NPs was evidenced by significant increases in caspases-8 and 9 activity and a decreased Bcl-2/Bax ratio. Furthermore, cell cycle arrest at the sub-G1 was noticed in the treated cells. Additionally, the NPs markedly inhibited the migration rate of MCF-7 cells. These findings suggest that CS-ZnO-Ber NPs induce cell-cycle arrest and activate the apoptotic pathways in MCF-7 cells, highlighting their potential as a hopeful therapeutic agent for breast cancer.